The Digital Art Scene of Public Spaces in the Age of the Metaverse: Case Study of Ooeli Art Park, Hangzhou, China - Liu, Dan (UNIMAS, 2025)
This PhD thesis examines the uniqueness of the digital art scene in the virtual space and its influence on traditional public art spaces and audience engagement. The study examines the digital art scene as a connection between reality and virtual environments, offering novel methods for art engagement. This paper employs qualitative research methods to examine how digital art may transform art presentation through technological innovation, act as a connection between virtual and public spaces, enhance art accessibility and innovation, and facilitate entry into the virtual realm to bolster the growth of associated industries. The study utilized the Ooeli Art Park project in Hangzhou, China, to gather interview data from artists, technology companies, art institutions, and visitors, highlighting critical factors and obstacles to the incorporation of digital art in public spaces. The findings indicate differing degrees of awareness and involvement within the digital arts community, highlighting the necessity for inclusive and accessible programming. The study thoroughly examines the influence of the digital art scene on urban environments and mass cultural communication from the viewpoints of urban research, art theory, and technology research. It offers guidance for global cities to enhance public spaces through digital technology, advocates for the convergence of art and technology, and introduces innovative concepts for the advancement of the cultural industry. The study forms a basic framework that suggests the digital art scene is a unique link between public art spaces and the virtual world. It also stresses how important interactive relationships are and provides a new way to understand and evaluate the progress of urban ecology and social dynamics.